Pemberian Intervensi Islami sebagai Upaya Meningkatkan Spiritualitas Pasien Gangguan Jiwa di RSKD Dadi Makassar - Sarmila; Ahmad Ridfah (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2022)
Mental disorders are a problem that is still common among the community. Individuals with mental disorders will experience an inability to carry out their functions and use in social life. Islamic intervention is a form of healing for mental patients with peace of mind and grace from God. The aim of the intervention is to increase the patient's awareness to remember God. Islamic intervention was given to inpatient mental patients at RSKD Dadi Makassar. The interventions used were in the form of lectures, reading the Koran, selawat, and praying together in delivering the material. During the activity, observations were made on the patient's behavior. The results obtained from the provision of Islamic intervention are changes in spirituality that lead to positive things, in mental patients at RSKD Dadi Makassar.